2021
DOI: 10.1111/ijcp.14044
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of the prognostic predictive models for patients with sepsis: Which model can be applied in clinical practice?

Abstract: Background: Sepsis is associated with high mortality and predictive models can help in clinical decision-making. The objective of this study was to carry out a systematic review of these models. Methods:In 2019, we conducted a systematic review in MEDLINE and EMBASE (CDR42018111121:PROSPERO) of articles that developed predictive models for mortality in septic patients (inclusion criteria). We followed the CHARMS recommendations (Critical Appraisal and Data Extraction for Systematic Reviews of Prediction Modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(427 reference statements)
2
3
0
Order By: Relevance
“…Our systematic review shows that existing models in the literature have a high risk of bias and low clinical applicability. These findings are consistent with others, a previous systematic review by Beneyto et al, 23 which identified and summarized, through the use of the PROBAST criteria the predictive models for predicting mortality in sepsis. The included studies showed a high risk of bias in the Participants, Predictors, Outcome and Analysis domains, with the risk of bias in the latter domain being high in 80%–100% of the studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our systematic review shows that existing models in the literature have a high risk of bias and low clinical applicability. These findings are consistent with others, a previous systematic review by Beneyto et al, 23 which identified and summarized, through the use of the PROBAST criteria the predictive models for predicting mortality in sepsis. The included studies showed a high risk of bias in the Participants, Predictors, Outcome and Analysis domains, with the risk of bias in the latter domain being high in 80%–100% of the studies.…”
Section: Discussionsupporting
confidence: 92%
“…20,21 Both tools have been widely used in several diseases, showing limitations and difficulty of models to be applied in clinical practice when they have biases. [22][23][24] As far as we know, no systematic review of prediction models of UBC mortality has been carried out with the application of CHARMS and PROBAST. [19][20][21] Hence, a summary of the existing models is lacking, including the description of the risk of bias in each model, to allow clinicians to better stratify the mortality risk of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, the authors provide a synthesis of the 19 prediction models identified. Among them, 52.6% showed low applicability and all of them had a high risk of bias; these findings agree with previous systematic reviews carried out with a similar methodology [6,14].…”
Section: Introductionsupporting
confidence: 90%
“…2 Thus, identifying clinical indicators that can predict severe neonatal infection early and effectively and establishing predictive models based on these indicators is of great clinical significance for the early diagnosis, control and improved prognosis of neonatal infection. [3][4][5] White blood cell count (WBC), CRP and PCT levels are currently used to diagnose and monitor neonatal infection, 6 white blood cells are essential components of the human immune system, responsible for identifying and eliminating pathogens such as bacteria, viruses, and parasites, when an infection occurs, white blood cells increase to counter the infection, platelets play a key role in coagulation and hemostasis while also participating in inflammatory responses. During an infection, the inflammatory response can lead to platelet activation and consumption, potentially resulting in a decreased platelet count, additionally, some infections (particularly bacterial infections) can cause a reduction in platelets as toxins or immune mediators produced by the pathogens may directly damage platelets or interfere with their production, but the sensitivity and specificity of any single peripheral blood index need to be studied further.…”
Section: Introductionmentioning
confidence: 99%